Transformation Strategy of Pesantren Wali Songo Ngabar in Responding to Modern Education - Wathoni, Kharisul (Program Studi Pendidikan Agama Islam, 2023)
Pesantren can now play a role and compete with educational institutions in general, especially in trying to adapt to the development and progress of the times. On the other side, manypesantren can stand on equal footing with general educational institutions in terms of mastery of science and technology. It is evidently an added value because, on the one hand, it remains a center for Islamic studies by trying to maintain old traditions that are still relevant, while on the other hand, it remains inclusive of various issues of change that occur outside the pesantren. The efforts of Pesantren to gain public trust are carried out in earnest to provide satisfaction to the community as